Fate of allogenic bone graft for sternal support in pectus excavatum repair. (October 2015) - Ashour, Mahmoud; Rafay, Mohommad; Saleh, Waleed; Ahmed, Mohamed; Robaidi, Hassan; Alamassi, Mohammad; Al Kattan, Khaled
Background: Techniques for pectus excavatum repair are based on sternal support using various implants that have been reported to cause complications including migration and perforation of adjacent vital organs. Thus the search for an ideal sternal support is ongoing. This study aimed to assess the feasibility and fate of allogenic bone grafts as a durable sternal support for pectus excavatum repair. Methods: Pectus excavatum deformities in 3 men were corrected by modified Ravitch repair using allogeneic bone grafts for sternal support. Postoperatively, the patients were followed up for 3 years. Chest computed tomography and bone scans were performed to identify radiological features relevant to the stability, viability, and fate of the bone grafts. Results: The postoperative course was uneventful in all patients. Cosmetic correction was rated as very good with patient satisfaction. Bone scans showed progressively increasing activity in the graft, indicating an ongoing process of neovascularization. Chest computed tomography showed not only bone resorption, new bone formation, and remodeling but also incorporation of the graft into the sternum and corresponding ribs through newly generated, normally configured sternocostal segments. Conclusions: As seen radiologically, this technique offers a model for sternal support that has the potential to incorporate into the host tissue through newly generated, normally configured sternocostal segments, without restriction of chest wall expansion, features that have not been previously reported.